PARTISIPASI MASYARAKAT DALAM PELESTARIAN HUTAN KOTA - Oot Hotimah (SPATIAL: Wahana Komunikasi dan Informasi Geografi, 2015)
ABSTRACT Bogor Botanical Gardens (BBGs) has a big role for carbonic emission reduction. Many functions of BBGs such as ecologycal, social and economic functions. The strategic function of BBGs needs more attention from Bogor’s citizen for its continuities. However based on the fact showed that exuberances of BBGs trees has decreased. Due to many cars passed by in BBGs area became crowded. there was reduction of bird species form 85 species (2002) become 35 species (2007). From this phenomena, it is not impossible if one day the trees at BBGs have snatched by human for getting some waters. The interviews were conducted to the BBGs visitors that they live in the city of Bogor. The investigation revealed that the active communications among BBGs officer with the society around it become an absolute requirement to conserve BBGs as rescue media of biodiversity crisis. The most important aspect is the role of the community for the success of the preservation of the BBGs as urban forest. Keyword: Urban forest preservation, Bogor Botanical Gardens.